Dugaan Delik Penodaan Agama dalam Pemulasaraan dan Penguburan Jenazah Akibat Covid-19 - Isnaini Imroatus Solichah; Hanif Nur Widhiyanti (Jurnal Hukum Lex Generalis, 2021)
Since the WHO declared that the Covid-19 outbreak had reached the level of a global pandemic, it had prompted governments in many countries to take urgent and aggressive action to immediately stop the spread of the deadly virus. Various policies are made and implemented by the governments of each country to control the spread of the disease. One of the concerns in Indonesia, where the majority of the population is Muslim, is the policy for the burial of corpses due to Covid-19. Taking into account that the corpse of a Covid-19 patient is a corpse infected with a contagious disease and must be handled specifically to protect the burial officers by still paying attention to the provisions of Shara' which are the rights of the corpse.